HUBUNGAN KONSUMSI JAJANAN YANG MENGANDUNG KARIOGENIK DENGAN KARIES GIGI PADA ANAK USIA 8-12 TAHUN DI MADRASAH IBTIDAIYAH AL-ISTIQOMAH DESA GUNTUNG PAPUYU KECAMATAN GAMBUT - Sarida Putri, Nesvy (Poltekkes Kemenkes Banjarmasin, 2022)
Elementary school children are an age group that is very critical of the occurrence of permanent dental caries. This age group is the transition period of milk teeth to permanent teeth, therefore many snacks at school with sweet foods and drinks can threaten dental health. The purpose of this study was to determine the relationship between the consumption of cariogenic-containing snacks and dental caries in children aged 8-12 years at Madrasah Ibtidaiyah Al-Istiqomah, Guntung Papuyu Village, Gambut District. This type of research is analytic observational with a cross sectional design. The population and research sample found 50 students by taking samples using the Total Sampling technique. The results showed that the consumption of snacks containing cariogenic in children aged 8-12 years was mostly in the less category (57.9%) and dental caries was mostly in the moderate category (54%). After being tested statistically with the Chi-Square test, the p value = 0.044 (p <0.05) In conclusion, there is a relationship between the consumption of cariogenic-containing snacks and dental caries in children aged 8-12 years at Madrasah Ibtidaiyah Al-Istiqomah, Guntung Papuyu Village, Gambut District. Suggestions for the need for counseling efforts regarding the consumption of good food for dental and oral health as well as fillings affected by caries and dental care that can still be functioned, so as to prevent further tooth decay.